Clinical Utility of Emergency Capsule Endoscopy for Diagnosing the Source and Nature of Ongoing Overt Obscure Gastrointestinal Bleeding - Iio, Sumio (Gastroenterol Res Pract, 2019)
BACKGROUND AND AIMS: In patients with ongoing overt obscure gastrointestinal bleeding (OGIB), prompt detection of the bleeding source is crucial to treatment success. However, there is no consensus on the optimal timing of diagnostic capsule endoscopy (CE). We investigated the clinical utility of emergency CE for detecting the source of ongoing overt OGIB. METHODS: We retrospectively evaluated 146 consecutive patients who, between February 2009 and July 2018, underwent emergency CE at Hiroshima University Hospital to detect the source of ongoing overt OGIB. Patients with a bleeding source located outside the small bowel were excluded. The remaining 127 patients were stratified according to the timing of CE relative to the onset of bleeding: patients in group A (n = 15, 12 men; mean age: 75 years; age range: 62–83 years) underwent CE within 48 hours of bleeding onset, whereas patients in group B (n = 112, 73 men; mean age: 65 years; age range: 17–88 years) underwent CE at >48 hours after bleeding onset. All patients underwent double-balloon endoscopy, and the final diagnosis was compared against the CE findings. RESULTS: The CE lesion detection rate was significantly higher in group A (12/15 patients, 80%) than in group B (53/112 patients, 47%) (p = 0.0174). There was no significant difference between the two groups regarding the patients' background characteristics. Vascular lesions were the most frequent finding in both groups. The diagnostic concordance rate between emergency CE and double-balloon endoscopy was 100% in group A and 92.9% in group B. Rebleeding after endoscopic treatment was confirmed in only one patient in group B. CONCLUSIONS: Emergency CE represents a useful diagnostic modality in patients with ongoing overt OGIB, potentially improving detection rates and reducing rebleeding risk.